O modelo de julgamento de casos repetitivos como técnica de gestão de processos : a fixação de tese jurídica e a eventual formação de precedentes - Silva, Larissa de Almeida (2019)
The mass reality in which is inserted the contemporary society results in the judicialization of a huge volume of repetitive demands and forces the procedural Law to occupy itself with aspects that go beyond the decision-making and the procedural activity, demanding the Judiciary to promote the management of demands in procedural progress as well in order to achieve the constitutional guarantees related to the jurisdictional function. The problem of the high number of demands is not new and the analysis of the procedural collection shows that it goes on in an ascending line and its motivations are not the ones related to the jurisdictional activity, but to the social, economic and institutional scenario in which the country is in. Therefore, the management of the jurisdictional function has gained protagonism in debates involving massified questions and won more space in the national legislation, according to the articles of the Code of Civil Procedure of 2015 related to the “Incidente de Resolução de Demandas Repetitivas” and to the reformulation of the repetitive “Recurso Extraordinário” and “Recurso Especial”. The research materialized in this study describes the model of judgement of repetitive cases based on a managerial perspective of the jurisdictional activity and on the efficiency vector of the Brazilian procedural protection. The study uses the deductive method and the presentation of the theme is made using a qualitative approach through the bibliographic and jurisprudential texts. It makes a true effort to demonstrate the optimizer function and the managerial scope scrutinized by the “Incidente de Resolução de Demandas Repetitivas” and the repetitive “Recurso Extraordinário” and “Recurso Especial” instruments.